Circulating bile acid profiles characteristics and the potential predictive role in clear cell renal cell carcinoma progression - Qi-Chao Wang; Jing-Yi Cao; Guang-Yue Wang; Heng Wang; Hua Peng; Qian Wang; Zhi-Xiang Yin; Jie-Zhou; Ping-An Chang; Gui-Hua Zhang; Wen-Tao Yao; Jia-Cheng Wu; et al. (BMC Nephrology)
Abstract Background The incidence of clear cell renal cell carcinoma (ccRCC) has steadily increased over the past decade, and recent studies have linked bile acid (BA) metabolism to its development. However, the metabolic profile of BAs and their potential as biomarkers in ccRCC pathogenesis remain poorly characterized, making their evaluation crucial for advancing disease understanding and management. Methods A total of 68 newly diagnosed ccRCC patients and 63 healthy controls were enrolled. Serum bile acid (BA) profiles were measured using Ultra Performance Liquid Chromatography-Tandem Mass Spectrometry (UPLC-MS/MS). The Orthogonal Projections to Latent Structures Discriminant Analysis (OPLS-DA) model analyzed differences in serum BA profiles between ccRCC patients and controls. Additionally, the relationship between BA profiles and tumor heterogeneity parameters was investigated. Receiver Operating Characteristic (ROC) analysis identified potential biomarkers for ccRCC pathogenesis. Results The BA profile was altered in ccRCC patients and was not influenced by sex or age. Specifically, primary and secondary unconjugated BA fractions were significantly higher in the ccRCC population. Five BA metabolite candidates exhibited the most significant differences between ccRCC patients and controls. Deoxycholic acid (DCA) was associated with pathological pTNM stage classification and grade. Chenodeoxycholic acid (CDCA) and lithocholic acid (LCA), combined with testosterone, showed potential as biomarkers for the pathogenesis of ccRCC. Conclusion Alterations in the serum BA profile are observed in ccRCC. Deoxycholic acid (DCA) correlates with pathological pTNM stage classification and tumor grade. Additionally, CDCA combined with LCA show potential as biomarkers for ccRCC pathogenesis. Clinical trial number Not applicable.